2011
DOI: 10.1080/07370016.2011.539080
|View full text |Cite
|
Sign up to set email alerts
|

Is It Worth It? Measuring the Long-Term Effects of an International Experience for Nursing Students in Ecuador

Abstract: In 1999, a community college in Florida initiated a study abroad program that included a transcultural nursing Web-based course and a 2-week clinical component in Ecuador. The investigator collected data from 36 participants using Zorn's International Education Survey to measure 4 dimensions of impact of the international experience. Results revealed that impact on the professional role dimension was most significant, followed by the international perspective dimension, the personal development dimension, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…[19][20][21][22] When long-term outcomes were measured quantitatively, the most significant influence was on how the experience shaped the nurses' perspectives on cultural, political, and international issues. 23 These findings are similar to those of a large, multi-university study of the long-term effect of study abroad across all disciplines, which showed that the experience can have lifetime effects. In particular, those whose study abroad included culture and language immersion, or internships in less common destinations, such as in the Middle East and Asia, reported life-long impact related to global engagement.…”
Section: Literature Reviewsupporting
confidence: 86%
“…[19][20][21][22] When long-term outcomes were measured quantitatively, the most significant influence was on how the experience shaped the nurses' perspectives on cultural, political, and international issues. 23 These findings are similar to those of a large, multi-university study of the long-term effect of study abroad across all disciplines, which showed that the experience can have lifetime effects. In particular, those whose study abroad included culture and language immersion, or internships in less common destinations, such as in the Middle East and Asia, reported life-long impact related to global engagement.…”
Section: Literature Reviewsupporting
confidence: 86%
“…Overall, the students' scores on the IES were very high when compared to Zorn () and others (DeDee & Stewart, ; Smith & Curry, ; Thompson et al., ) (See Table ), where participants were surveyed 3 to 15 years postexperience. Only one study (Thompson et al., ) included participants who had not graduated ( N = 31, 42%).…”
Section: Discussionmentioning
confidence: 63%
“…Overall, Zorn () and others (DeDee & Stewart, ; Smith & Curry, ; Thompson et al., ) have reported a positive long‐term impact (anywhere from 3 months to 15 years) of international experiences on nursing students. Scores on each dimension also have highlighted the positive impact, although the rank order of dimensions has varied across studies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A summary of other benefits of study abroad cited in the literature include a broader understanding of the social determinants of health and their impact on health care delivery systems (Egenes, 2012;Kent-Wilkinson et al, 2010;Kokko, 2011); first-hand experiences of issues or factors that influence health and social inequities (Kulbok et al, 2012;Smith and Curry, 2011); increased awareness of global health issues and the development of global citizenship (Mill et al, 2010;Kulbok et al, 2012); increased cultural awareness and the development of cultural competence/safety (Aseno et al, 2013;Bentley and Ellison, 2007;Kelleher, 2013;Kokko, 2011;Ruddock and Turner, 2007;Smith-Miller et al, 2010); professional and personal growth (Kelleher, 2013;Kollar and Ailinger, 2002;Zorn et al, 1995); increased cognitive development (Kelleher, 2013); and long term positive impact on nursing practice (Kollar and Ailinger, 2002;Smith and Curry, 2011;Zorn, 1996).…”
Section: Relevant Nursing Researchmentioning
confidence: 99%